Metal Oxide Coated Optical Fiber For Humidity Sensing Application: A Review - Siti Nasuha Mustaffa; Tan Sin Jin; P. Susthitha Menon; Mohd Zulhakimi Ab Razak; Arni Munira Markom; Hazlihan Haris; Ismail Saad; Ahmad Razif Muhammad; Affa Rozana Abdul Rashid (IEEE, 2024)
Indexed by Scopus/ERA